1983
DOI: 10.1161/01.hyp.5.4.460
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic pressor responses and salt-induced hypertension in Dahl rats.

Abstract: Interactions between abnormal salt intake and central sympathetic function were studied by recording pressor and sympathetic effects of hypothalamic stimulation in Dahl salt-resistant (DR) and salt-sensitive (DS) rats. All DS rats, including those fed a low-salt diet since weaning, became hypertensive by 11 weeks of age. Increased salt intake aggravated hypertension in DS rats without affecting blood pressure in DR rats. Basal sympathetic tone determined during urethane anesthesia, from the frequency of splanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
2

Year Published

1984
1984
1994
1994

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 26 publications
3
11
2
Order By: Relevance
“…38 Taken together, these observations are consistent with the hypothesis that protection against the development of hypertension in DR fed high NaCl is related to inhibition of sympathetic nervous system activity. VOL 12, No 6, DECEMBER 1988 In contrast, in the DS dietary NaCl loading has been reported to potentiate the increment of vascular resistance in response to sympathetic nerve stimulation 39 and electrical stimulation of the ventromedial hypothalamus, 40 to increase the rate of basal neural firing of the splanchic nerve, 40 and to exacerbate impairment of baroreceptor reflex control of heart rate. 4142 Augmentation of cardiac norepinephrine turnover rate by NaCl loading, after the onset of hypertension, has also been reported in other models of salt-dependent hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…38 Taken together, these observations are consistent with the hypothesis that protection against the development of hypertension in DR fed high NaCl is related to inhibition of sympathetic nervous system activity. VOL 12, No 6, DECEMBER 1988 In contrast, in the DS dietary NaCl loading has been reported to potentiate the increment of vascular resistance in response to sympathetic nerve stimulation 39 and electrical stimulation of the ventromedial hypothalamus, 40 to increase the rate of basal neural firing of the splanchic nerve, 40 and to exacerbate impairment of baroreceptor reflex control of heart rate. 4142 Augmentation of cardiac norepinephrine turnover rate by NaCl loading, after the onset of hypertension, has also been reported in other models of salt-dependent hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…29 Further intracerebral ventricular injection of hypertonic NaCl solution or angiotensin II produces greater pressor responses in DS than DR rats even before the development of hypertension. 30 Koepke et al 31 have identified an important interaction between environmental factors (such as stress and dietary salt) and genetic factors in the central nervous system control of renal function in DS rats.…”
Section: -88 Supplement I Hypertension Vol 17 No 1 January 1991mentioning
confidence: 98%
“…2 - 4 Brain OLA content is higher in spontaneously hypertensive rats (SHR) than Wistar-Kyoto (WKY) rats, and high sodium intake further increases brain OLA in SHR. 4 Augmented sympathetic activity has been documented in several forms of sodiumdependent hypertension, including Dahl salt-sensitive (DS) rats 5 and SHR. 6 Brain OLA may play a primary role in mediating the sympathoexcitatory and hypertensive effects of high sodium intake in SHR 7 and DS rats.…”
mentioning
confidence: 99%